Exploration of Family Rutaceae in Garden Eden 100 Tobasa Agrowisata Forest - Nurhasnah Manurung; Pandu Prabowo Warsodirejo (UNIVERSITAS NEGERI PADANG, 2019)
Research in the Eden 100 agrotourism forest located in the area of Lumban Rang, Sionggang Utara Village, LumbanJulu District, Kab. Toba Samosir North Sumatra has been carried out for 3 months using